From Caá-ehé to a commercial sweetener – the diterpenoid glycosides of Stevia rebaudiana. (1st December 2016) - Hanson, James
The isolation, structure elucidation, chemistry, biosynthesis and biological activity of the sweet steviol glycosides from Stevia rebaudiana, are reviewed.